Bio-mechanical analysis of a Dollyo Chagi kick to determine the best area of contact to deliver the greatest energy - Goonaratne, Merennage Francis Susith S.W.; Bohez, Erik L.J.; Athakorn Kengpol; Than Lin (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
There are many variation of the basic Dolloy Chagi kick. As well as many studies around factors such as kicking distance or average force and speed of the kick. However there is little to no research done on the effect that kicking with the shin has compared with kicking with the foot. Thus an experiment was designed and conducted using a spring based apparatus with video analysis to find the force and energy transfer of kicks when performed with the shin and with the foot. The results were statistically tested for their significance, and a conclusion was drawn stating that the foot generates a greater impact force while the shin transfers more energy to the target.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Industrial Engineering, School of Engineering and Technology
Capstone Project (B.Sc.) - Asian Institute of Technology, 2017
Keywords: Biomechanics -- Measurement; Kinesiology